2018
DOI: 10.1111/tri.13125
|View full text |Cite
|
Sign up to set email alerts
|

Access to kidney transplantation in European adults aged 75-84 years and related outcomes: an analysis of the European Renal Association-European Dialysis and Transplant Association Registry

Abstract: To what extent access to, and allocation of kidney transplants and survival outcomes in patients aged ≥75 years have changed over time in Europe is unclear. We included patients aged ≥75-84 years (termed older adults) receiving renal replacement therapy in thirteen European countries between 2005 and 2014. Country differences and time trends in access to, and allocation of kidney transplants were examined. Survival outcomes were determined by Cox regression analyses. Between 2005 and 2014, 1392 older adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…The risk of early mortality after transplantation, compared with matched dialysis patients, was lower in patients with preemptive transplantation and those without cardiovascular comorbidity or diabetes. As reported previously, the most common causes of posttransplant deaths, after infectious diseases and malignancies, were cardiovascular diseases . Cardiovascular comorbidities should therefore continue to be a criterion for waiting‐list selection.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The risk of early mortality after transplantation, compared with matched dialysis patients, was lower in patients with preemptive transplantation and those without cardiovascular comorbidity or diabetes. As reported previously, the most common causes of posttransplant deaths, after infectious diseases and malignancies, were cardiovascular diseases . Cardiovascular comorbidities should therefore continue to be a criterion for waiting‐list selection.…”
Section: Discussionmentioning
confidence: 60%
“…Because the number of people aged ≥70 on KT waiting lists has been increasing, several studies have been able to examine their outcomes . Using the Scientific Registry of Transplant Recipients (or SRTR), Rao et al analyzed data from patients wait‐listed between 1990 and 2004 at age ≥70 and reported that transplant recipients had an overall risk of death 41% lower than wait‐listed candidates, but with a risk of death during the first 45 days after transplant around twice as high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, during our study period, the mortality rate in the general population decreased, whereas the mortality rate in kidney transplant patients remained stable or slightly increased, contributing to an increase in excess mortality. The lack of improvement of the mortality rate in transplant patients may be explained by the increased acceptance of older patients for kidney transplantation, 38 as well as by greater acceptance of older and marginal kidney donors. 39 In kidney transplant recipients, the excess mortality remained stable over time for nearly all specific causes of death.…”
Section: Trends In Dialysis Patientsmentioning
confidence: 99%